Deep-hole blasting roof cutting technology for pressure relief in the final mining phase of the working face: a case study - Liu, Baomin; Chen, Dingchao; Xu, Changtao (Frontiers in Earth Science, 2025)
In the final mining phase of the working face, a large area of suspended roof can lead to stress concentration from mining-induced stress, which in turn causes deformation and instability of the main roadway. This study takes the Ji-17-21080 working face of the Pingdingshan No. 2 Mine as the engineering background, analyzing the structural characteristics of the main roof layer and the distribution of the advanced support stress, while revealing the principle of roof cutting and pressure relief for protecting the main roadway. Further, a FLAC3D numerical model was established based on the on-site geological conditions. The stress of the surrounding rock and the deformation characteristics of the main roadway were compared under four scenarios: (1) a stop-mining coal pillar width of 120 m (no roof cutting line), (2) a stop-mining coal pillar width of 60 m (no roof cutting line), (3) a stop-mining coal pillar width of 60 m with one roof cutting line, and (4) a stop-mining coal pillar width of 60 m with two roof cutting lines. The simulation results indicate that reducing the width of the stop-mining coal pillar significantly increases the mining-induced effects on the main roof. However, the implementation of roof cutting measures effectively interrupts the stress transmission path of the advanced support, improving the stress environment. Furthermore, compared to a single roof cutting line, the synergistic effect of two roof cutting lines is more beneficial. Finally, two roof cutting lines were designed for deep-hole blasting and pressure relief at the Ji-17-21080 working face. Field monitoring results showed that the deformation of the air return downhill remained within controllable limits, ensuring the safe operation of the next working face in the mining area.